Seizure due to multiple drugs intoxication: a case report - Gulec,Handan (2016)
Abstract The mechanism of the antidepressant effect of bupropion is not fully understood. Besides, using it in the treatment of depression, it is found to be effective in reducing withdrawal symptoms due to smoking cessation. A 28-year-old female patient with a history of depression was admitted to emergency department an hour after ingestion of bupropion, quetiapine, and levothyroxine in high doses to commit suicide. While accepting her into the Intensive Care Unit, she was awake, alert, disoriented and agitated. After 2 h, the patient had a generalized tonic-clonic seizure. The necessary treatment was given and 9 h later with hemodynamic improvement, the patients’ mental status improved. Bupropion may cause unusual behaviors such as delusions, paranoia, hallucinations, or confusion. The risk of seizure is strongly dose-dependent. We want to emphasize the importance of early gastric lavage and administration of activated charcoal.